Open Access Redefined: Survey Data and Literature Study on the Impact of Sci-Hub in Orthopaedic Research - Gathen, Martin; Cucchi, Davide; Kabir, Koroush; Welle, Kristian; Jaenisch, Max; Jansen, Tom Rainer; Randau, Thomas Martin (Zeitschrift für Orthopädie und Unfallchirurgie, 2022)
Background Since Alexandra Elbanyan founded Sci-Hub in 2011, the website has been used by a growing number of researchers worldwide. Sci-Hub is a so-called shadow library or guerrilla open access format bypassing publishers’ paywalls, giving everyone free access to scientific papers. Until today, there have been no publications about usage by orthopaedic and trauma surgeons of Sci-Hub or other “pirate sites” and how it may influence their work.Materials and Methods Orthopaedic and trauma surgeons of four university hospitals in Germany and Europe were consulted using a standardised questionnaire containing multiple items about the use and evaluation of Sci-Hub. In addition, the Medline and Cochrane databases were screened for all studies related to Sci-Hub. Two reviewers independently reviewed all articles and the references of these articles.Results Of all orthopaedic surgeons consulted, 69% knew of Sci-Hub and 66.7% used it on a regular basis. Of the younger participants (< 45 years old), 77% knew the webpage, while only 25% of older participants (> 45 years old) knew the webpage. Ninety percent found the quality of their citation and research had been enhanced since using Sci-Hub. On a scale of 1 to 10, user-friendliness was rated with a mean rating of 7.58 (95% CI: 7.262–7.891). Ethical or legal concerns among users seem mixed. On a scale of 1 (no concerns) to 5 (many concerns), the mean score was 2.39 (95% CI: 2.154–2.615). Of doctors using Sci-Hub, 89% would recommend it to other colleagues.Conclusion The quality and number of articles in Sci-Hub is outstanding, and the rate of young researchers using the website is high. The most important shift in literature research for decades is a phenomenon mostly used by young researchers and is not the subject of current research itself. Sci-Hub may have already changed how orthopaedic research works.
Keywords: Sci-Hub; Internet research; shadow library; open access; piracy